On initial coefficient inequalities for certain new subclasses of bi-univalent functions - Uday H. Naik; Amol B. Patil (Journal of the Egyptian Mathematical Society, 2017)
In the present paper, we introduce two interesting subclasses of the class of bi-univalent functions defined on the open unit disk U and obtain improved estimates on the initial coefficients |a2|, |a3| and |a4| for the functions in these subclasses.